Intelligent Tutoring System - Fitria Amastini (ULTIMA InfoSys, 2014)
Intelligent Tutoring System is a tutor behaviour system which can be used as an alternative goal for interactive e-learning and distant learning. This system can provide an adaptive system to support student’s learning and retention process based on their characteristic and needed. There are development method such as bayesian network, and neural network that can build fundamental component of Intelligent Tutoring System. This paper will give some concepts and examples for implementing those method from other papers. Index Terms—intelligent tutoring system, artificial intelligent, neural network, bayesian network, ontology